2013
DOI: 10.1016/j.juro.2012.09.095
|View full text |Cite
|
Sign up to set email alerts
|

Role of Opioid and Metabotropic Glutamate 5 Receptors in Pudendal Inhibition of Bladder Overactivity in Cats

Abstract: Purpose We determined the role of opioid and metabotropic glutamate 5 receptors in the pudendal inhibition of bladder overactivity. Materials and Methods Cystometrograms were performed in 11 cats under α-chloralose anesthesia by slowly infusing the bladder with saline or 0.25% acetic acid. Pudendal nerve stimulation at intensities of multiple times the threshold to induce observable anal twitching was applied during cystometrogram to inhibit the bladder overactivity induced by acetic acid irritation. Naloxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 19 publications
8
39
0
4
Order By: Relevance
“…Post hoc paired comparisons with Bonferroni correction showed that while normalized bladder pressure was significantly higher with picrotoxin (*P Ͻ 0.001), there was no significant difference between control, paralytic, and washout trials. contributions of opioidergic mechanisms to stimulationevoked bladder inhibition (7,28). The present results reveal that a spinal GABAergic mechanism mediates the inhibitory pudendovesical pathway.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Post hoc paired comparisons with Bonferroni correction showed that while normalized bladder pressure was significantly higher with picrotoxin (*P Ͻ 0.001), there was no significant difference between control, paralytic, and washout trials. contributions of opioidergic mechanisms to stimulationevoked bladder inhibition (7,28). The present results reveal that a spinal GABAergic mechanism mediates the inhibitory pudendovesical pathway.…”
Section: Discussionmentioning
confidence: 54%
“…Inhibition of bladder contractions evoked by the infusion of AA, but not saline, with tibial nerve stimulation was blocked by naloxone (44). Later experiments demonstrated that naloxone had no effect on pudendal stimulation-evoked inhibition of bladder overactivity in cats (28). We found that inhibition by either PN or DNP stimulation remained intact following administration of naloxone across a range of doses and stimulation amplitudes.…”
Section: Other Mechanisms May Not Be Necessary For Bladder Inhibitionmentioning
confidence: 55%
See 3 more Smart Citations